Novel layout of a bi-metallic nanoring for magnetic field pulse generation from light - Vienne, Guillaume (2015)
Recently Tsiatmas et al proposed using a nanoring made of two different metallic sectors to generate a magnetic pulse from a laser pulse [1]. Non-uniform heating of the ring creates very large temperature gradients, which drive thermoelectric currents, and this creates a localized magnetic field. However, heat from the laser pulse may result in the melting of the nanoring. We propose a symmetric structure made of four metallic sectors, which results in a higher magnetic field generation together with a lower lattice temperature. We also show that the magnetic field depends strongly on the size of the metallic sectors and interpret the results with the help of the electromotive forces, the overall ring resistance, and Biot–Savart law.